Development of an online broadband impedance spectroscopy extraction system of PV modules through switch-mode converters - Shelembe, Lindani (Department of Electrical Engineering, 2024)
Solar PV systems have traditionally relied on terminal DC current and voltage characteristics for online diagnostics. This approach monitors the current and voltage levels of a module, and a change in these levels indicates a system anomaly. However, this information only alerts to a decrease in the current or voltage levels, but not the possible cause(s) for the anomaly. To enable more detailed online diagnostics, linear impedance spectroscopy, a frequency-based characterization technique implemented through a DC-DC switch-mode converter, has been shown to provide fast and reliable impedance information that can be utilized to diagnose the condition of batteries and fuel cells in real-time. However, the implementation of this technique in a PV system presents challenges that have not been identified or addressed in current research. To develop such a system for a solar PV module, an excitation source with wide loop bandwidth capabilities is required to account for the broader impedance bandwidth of a PV module compared to batteries or fuel cells. The excitation signals must be designed such that they can minimize the nonlinearities observed at lower and higher frequencies, which result from induced excitation produced by the nonlinear DC-DC switch-mode converter.